Point-of-Care Procedure for Enhancement of Meniscal Healing in a Goat Model Utilizing Infrapatellar Fat Pad–Derived Stromal Vascular Fraction Cells Seeded in Photocrosslinkable Hydrogel. Issue 14 (December 2019) - Rothrauff, Benjamin B.; Sasaki, Hiroshi; Kihara, Shinsuke; Overholt, Kalon J.; Gottardi, Riccardo; Lin, Hang; Fu, Freddie H.; Tuan, Rocky S.; Alexander, Peter G.
Background: Large radial tears of the meniscus involving the avascular region can compromise meniscal function and result in poor healing and subsequent osteochondral degeneration. Augmentation of surgical repairs with adipose-derived stromal vascular fraction (SVF), which contains mesenchymal stromal cells, may improve meniscal healing and preserve function (ie, chondroprotection). Purposes: (1) To develop a goat model of a radial meniscal tear with resulting osteoarthritis and (2) to explore the efficacy of a 1-step procedure utilizing infrapatellar fat pad–derived SVF cells seeded in a photocrosslinkable hydrogel to enhance meniscal healing and mitigate osteochondral degeneration. Study Design: Controlled laboratory study. Methods: A full-thickness radial tear spanning 90% of the medial meniscal width was made at the junction of the anterior and middle bodies of the goat stifle joint. Tears received 1 of 3 interventions (n = 4 per group): untreated, repair, or repair augmented with photocrosslinkable methacrylated gelatin hydrogel containing 2.0 × 10 6 SVF cells/mL and 2.0 µg/mL of transforming growth factor β3. The contralateral (left) joint served as a healthy control. At 6 months, meniscal healing and joint health were evaluated by magnetic resonance imaging (MRI) and assessed by histological and macroscopic scoring. The Whole-Organ Magnetic Resonance Imaging Score and the presence of a residual tear, as evaluated with T2 MRI sequences, were determined by a single blinded orthopaedic surgeon. Results: When compared with tears left untreated or repaired with suture alone, augmented repairs demonstrated increased tissue formation in the meniscal tear site, as seen on MRI and macroscopically. Likewise, the neotissue of augmented repairs possessed a histological appearance more similar, although still inferior, to healthy meniscus. Osteochondral degeneration in the medial compartment, as evaluated by the Whole-Organ Magnetic Resonance Imaging Score and Inoue (macroscopic) scale, revealed increased degeneration in the untreated and repair groups, which was mitigated in the augmented repair group. Histological evaluation with a modified Mankin score showed a similar trend. In all measures of osteochondral degeneration, the augmented repair group did not differ significantly from the uninjured control. Conclusion: A radial tear spanning 90% of the medial meniscal width in a goat stifle joint showed poor healing potential and resulted in osteochondral degeneration by 6 months, even if suture repair was performed. Augmentation of the repair with a photocrosslinkable hydrogel containing transforming growth factor β3 and SVF cells, isolated intraoperatively by rapid enzymatic digestion, improved meniscal healing and mitigated osteoarthritic changes. Clinical Relevance: Repair augmentation with an SVF cell–seeded hydrogel may support successful repair of meniscal tears previously considered irreparable.